Fatty Acid Composition of Microwave Cooked Pangasius Meat Studied by Gas Chromatography - Kothandaperumal, S. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Pangasius catfish culture is widely practiced in India. It has low cost of production, fast growth rate and disease resistance, more freshness, Good market potential in interior areas, especially in restaurants and hotels but it has more fat and hence has an unusual odour, when consumed in processed form affects the marketability and further value addition Also the nutritional value of catfish lipids is low because of a small amount of n-3 family PUFA and high amount of MUFA and SFA. The SFA and Trans C18:1 MUFA can increase risk of chronic cardiovascular diseases that affects the heart, blood vessels, and brain. Effective processing method can get rid of the fat content in Pangasius catfish fillet and provide a good protein food for consumers. The present project is therefore proposed to develop a suitable preprocessing method for removal of fat from catfish fillets. Heat treatment such as microwave methods were used to reduce in the SFA and MUFA content of fish fillets. The present research is proposed to standardize the different time and temperature of cooking process of defatted fillets. This research proposed on study of saturated and mono-unsaturated fatty acid from different heat treatment meats.